Colonialism and neocolonialism - Sartre, Jean-Paul (Routledge, 2001)
Colonialism and Neo-Colonialism is a classic critique of France's policies in Algeria in the 1950s and 1960s and inspired much subsequent writing on colonialism, post-colonialism, politics, and literature. It includes Sartre's celebrated preface to Fanon's classic Wretched of the Earth. Colonialism and Neo-Colonialism had a profound impact on French intellectual life, inspiring many other influential French thinkers and critics of colonialism such as Jean-Francois Lyotard, Frantz Fanon, Pierre Bourdieu and Jacques Derrida.